PENGARUH BIOCHAR TONGKOL JAGUNG DIPERKAYA AMONIUM SULFAT [(NH4)2SO4] TERHADAP KEMANTAPAN AGREGAT TANAH, BEBERAPA SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN JAGUNG - Endang Listyarini; Yoga Prabowo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Soil fertility is the ability of soil to supply nutrient for plant. The availability of nutrients in soil is one of factors to support the success of plant growth. The addition of corn cob biochar with ammonium sulfate increases the availability of nutrients in soil. Soil conditioner is natural compound that can improve soil fertility so it can support the plant growth. The treatments tested were application of ammonium sulfate in corn cob biochar, biochar, NPK, manure, and control. The doses of fertilizers were urea 120 g/plot, TSP 240 g/plot, KCl 160 g/plot, manure 5 kg/plot, corn cob biochar 8 kg/plot, and the addition of ammonium sulfate in corn cob biochar 8 kg/plot. The parameters observed were soil aggregate stability, pH, C-organic, CEC, and total-N. Plant growth was measured based on plant height and leaf. The results showed that biochar treatment with ammonium sulfate had the best outcome and was able to improve soil aggregate stability up to 56%, pH 14%, C-organic 24.8%, CEC 57%, and total-N up to 18%. Besides, this treatment had the best result to the plant height in second week up to 50%, forth week 20%, sixth week 42%, eight weeks 46% and tenth week 40%. Enhancement of total leaf was up to 37% in second week, 22% in fourth week, 44% in sixth week, 35% in eighth week and 29% in tenth week.